Mobile Virtual Laboratory in Nigeria (International Journal of Engineering and Computer Science, 2018)
This research has explored the use of Mobile Virtual Laboratory (MVL) for laboratory practicals in institutions of higher learning in Nigeria by designing, implementing and evaluating the developed MVL cross-platform application that works on different mobile operating systems, contrary to previous research works that deployed virtual laboratories for only specific mobile operating systems. A cross-platform Mobile Virtual Laboratory architectural framework was developed with the client side in Java and the server side in PHP. This had four layers which were application server, database server, client (Mobile device) and the admin console and the Rapid Application Development (RAD) model was used. Thereafter science laboratory practicals were uploaded and one hundred and twenty students were purposively selected to evaluate its implementation. A user evaluation of the mobile virtual laboratory developed was conducted to evaluate its usability, conceptual learning and re-usability. Using the Fiedman’s test, a significant relationship was found between Mobile Virtual laboratories and conceptual learning, and also with re-usability, whereas no significant relationship was observed with usability. Analysis of this study indicates that while there is important evidence in Nigeria that there is an increase in the usage of mobile devices, more research work needs to be carried out on how it can be used positively to impact educational outcomes. This research demonstrated the superiority of the developed framework over other existing techniques for it being a cross-platform solution. Though targeted at tertiary institutions it could be integrated into teaching science laboratory practicals at all levels.